2021
DOI: 10.1007/s12517-021-09230-5
|View full text |Cite
|
Sign up to set email alerts
|

Field study of a new ecological slope protection method applied to expansive soil slope

Abstract: This paper used a new type of ecological slope protection method-anchor reinforced vegetation system (ARVS) for shallow protection of the expansive soil slope. We established a test slope with different protection measures in the suburbs of Nanning; the artificial simulated rainfall tests and comprehensive in situ monitoring were carried out on the slope. The protective effect and mechanism of ARVS on expansive soil slopes under the action of rainfall were systematically studied. The results showed that the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Limitation of swelling-shrinkage deformation 1. Flexible limitation method (e.g., Geogrids [128], geo-cells [130], soilbags [115], ARVS [131,132]).…”
Section: Protection Principles Methods and Materials Effects Analysis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Limitation of swelling-shrinkage deformation 1. Flexible limitation method (e.g., Geogrids [128], geo-cells [130], soilbags [115], ARVS [131,132]).…”
Section: Protection Principles Methods and Materials Effects Analysis...mentioning
confidence: 99%
“…The previously described soilbag stabilization method prevents rainwater infiltration and limits the lateral deformation of expansive soil [115]. Xu et al [131,132] proposed an anchor-reinforced vegetation system (ARVS) consisting of vegetation, anchors, and high-performance turf reinforcement mats (HPTRMs). The results indicated that this system effectively prevented large fluctuations in soil water content, restrained the swelling-shrinkage deformation of slopes (Figure 10), and provided superior slope protection [133].…”
Section: Limitation Of Swelling-shrinkage Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the maximum slope displacement gradually increases. The root systems of vegetation form a chain reaction with soil particles [30], which enhances the shear resistance of the surface soil, restraining the upward movement of the zone where shear strength decreases.…”
Section: Effect Of Reinforced Oleander Root System On Slope Displacementmentioning
confidence: 99%
“…Therefore, combining traditional slope protection techniques with ecological slope protection techniques can make up for the shortcomings of a single slope protection method. Xu et al used the anchor reinforced vegetation system for shallow protection of expansive soil slopes to effectively improve the soil and water conservation performance of the slope [16]. Su et al adopted the new slope protection method of bolt hinge anchor block and ecological vegetation coverage to effectively improve the slope stability [17].…”
Section: Introductionmentioning
confidence: 99%